Anti-CD3 Stimulated T Cell Transcriptome Reveals Novel ncRNAs and Correlates with a Suppressive Profile - do Almo, Manuela M.; Sousa, Isabel G.; da Silva, Waldeyr Mendes Cordeiro; Gatter, Thomas; Stadler, Peter F.; Hoffmann, Steve; Maranhão, Andrea Q.; Brigido, Marcelo (Anais do Simpósio Brasileiro de Bioinformática (BSB); 2020: Anais do XIII Simpósio Brasileiro de Bioinformática, 2020)
T lymphocytes are key players in immunity. Anti-CD3 antibodies activate T cells and promote a suppressive phenotype in vivo. Although the pharmacological use of these antibodies is widely studied, the underlying mechanisms are still poorly understood. Here we describe the response of the non-coding RNA transcriptome of T cells after in vitro stimulation of peripheral blood mononuclear cells (PBMC) by anti-CD3 and demonstrate that several novel long non-coding RNA are associated with antibody treatment. Regulated long intergenic non-coding RNAs were associated with lymphocyte activation and signaling pathways. In particular the lncRNA transcripts WFDC21P and GAPLINC are regulated in stimulated T cell.